The Global Drug Landscape Policy, Enforcement, and Innovation in the 21st Century - Phoong Seuk Wai; Phoong Seuk Yen (2026)
The global drug trade is one of the most complex and pressing challenges of our time, nearly every country and affecting lives. From shifting patterns of drug production and distribution to the evolution of national and international policies, the drug landscape is constantly changing driven by political, economic, social, and technological forces. This book was conceived out of a need to better understand these changes and to provide a comprehensive, interdisciplinary view of the global drug phenomenon.This book brings together insights from criminology, public policy and technology to examine the past, present, and future of drug-related issues. It explores regional case studies, policy models, enforcement strategies, and the growing role of innovation from artificial intelligence and big data to the rise of online drug markets. The book also assesses the role of public health in shaping more humane and balanced responses.It is our hope that this book will serve as a valuable resources for researchers, policymakers, educators, legal professional, and community leaders. By presenting both empirical evidence and forward-looking perspectives, this book aim to contribute to ongoing conversation and efforts toward more effective, equitable, and infored drug policy frameworks.